New Vision in Photoprotection and Photorepair - Marie-Therese Leccia; Celeste Lebbe; Jean-Paul Claudel; Mridvika Narda; Nicole Basset-Seguin (Adis, Springer Healthcare, 2019)
Abstract Chronic exposure to solar radiation is associated with an increased incidence of skin cancer worldwide and more specifically with non-melanoma skin cancers and actinic keratosis. At the cellular level DNA damage is the main event following ultraviolet (UV) exposure. The kind of lesions produced depends on the wavelength and the energy profile of the radiation, with different photoproducts being formed as a result. Although endogenous DNA repair mechanisms are somewhat effective in repairing DNA, some DNA damage persists and can accumulate with chronic exposure. UV protection strategies, such as sunscreen use, are important in limiting further DNA damage. Several published studies have demonstrated the protective effect that regular use of sunscreen can have against the development of skin cancers. Newer options that aim to help repair damaged DNA may have an important role in reducing the incidence of chronic sun exposure-related photoaging and non-melanoma skin cancers. Photolyase, which is capable of repairing cyclobutane dimers formed as a result of DNA irradiation, is one such novel ingredient. In the first part of this paper we review the rationale for a combined treatment approach of photoprotection and photorepair with photolyase. In the second part we evaluate several published clinical studies, which suggest a beneficial effect in preventing new skin lesions in photodamaged skin. A strategy of photoprotection plus photorepair appears to be relevant for all persons with a high level of solar exposure and those at a higher risk for developing skin cancers.